PERAN LITERASI DIGITAL DALAM PENCAPAIAN SDGS 2030: PERSFEKTIF PENDIDIKAN & PENGEMBANGAN MASYARAKAT - Muhammad Eka Enyanto; Bilal Ali Akbar, Ichsan Fauzi Rachman (CV. ADIBA AISHA AMIRA, 2024)
Education and development have experienced significant changes in the digital era, requiring digital literacy to understand and use information and communication technology (ICT) wisely and ethically. Digital literacy plays an important role in achieving the 2030 Sustainable Development Goals (SDGs), especially in improving the quality of education and empowering communities. This research aims to explore the implications of digital literacy for achieving SDGs 2030, with a focus on inclusive education and community development. The literature review method was used with a qualitative approach to investigate the relationship between digital literacy, education, community development, and the achievement of SDGs 2030. Research findings show that digital literacy contributes to increasing access to education, innovation, gender equality, and economic empowerment, as well as increasing awareness of issues. -environmental issues and sustainable development. A comprehensive digital literacy approach, including digital-based education, digital literacy policies in the education sector, innovations such as Service Strategies for Students and Teachers Through Digital Literacy Culture, and training programs, have proven successful in increasing people's skills and awareness. Collaboration between stakeholders is needed to increase digital literacy at all levels, so that it can support the achievement of sustainable development goals globally. In the era of digital transformation, a better understanding of the role of digital literacy is key in achieving sustainable development goals in the future.